PENGEMBANGAN MODUL KURIKULUM MERDEKA BERBASIS GEOBOARD DAN APLIKASI GEOGEBRA UNTUK MENGATASI KESULITAN GEOMETRI DI SD: Pengembangan modul ajar dan keefektifan modul ajar - Riska Indah; Salmaini Salmaini; Syafri Ahmad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The research on the development of independent curriculum modules based on geoboards and geogebra applications aims to overcome the difficulties faced by students in learning geometry, precisely in recognizing the shape of flat buildings in grade 1. This study uses a development research method with a 4D development model (Define, Design, Develop, and Disseminate). The development process of this teaching module is carried out in 4 stages starting from the definition stage (Define), then the design stage (Design), then the development stage (Develop) and finally the dissemination stage (Disseminate). With these stages, researchers can create and develop independent curriculum teaching modules based on geoboard media and geogebra applications. The effectiveness of the teaching modules designed and developed can be seen through the results of validation and the results of dissemination in SDIT schools. Based on the results of the validation, it can be found that the teaching module that is designed still needs improvement and after improvement, the teaching module is effective and suitable for use in mathematics learning about recognizing the shape of flat building in the first grade and based on the results of the test the teaching module is not only able to overcome students' difficulties in learning mathematics but also increases student activity in learning, This can be seen from the response of students who received a positive response from students after conducting a trial of the independent curriculum module based on geoboard media and geogebra applications.